Early social conditions affect female fecundity in hermaphrodites - Cannarsa, Elio (Curr Zool, 2015)
Social conditions experienced prior to sexual maturity influence reproduction later in life in many animals. In simultaneous hermaphrodites, variation in mating group size influences reproductive investment. As the mating group size increases, reproductive resources devoted to the female function decrease in favor of the male function. Prior to sexual maturity, many hermaphrodites have a protandrous phase during which they produce sperm and can fertilize hermaphrodites’ eggs. In the simultaneously hermaphroditic polychaete worm Ophryotrocha diadema, the cost of male reproduction during adolescence is spread over the whole energy budget of worms as shown by a reduced growth rate, a delayed age at sexual maturity and the shortening of life span compared to protandrous males that do not reproduce. Little is known on whether social conditions experienced during development affect reproductive investment of immature individuals. We investigated whether social conditions affected the length of the protandrous phase, body size and also the subsequent female fecundity of same-age protandrous individuals of O. diadema, which did not had to face competition for egg fertilization. Results show that in large group sizes protandrous males lengthened their protandrous phase, slowed down body growth and decreased their individual investment at the first egg laying compared to protandrous males that were reared in isolation. In the successive egg layings worms adjusted their egg output to the current social conditions. We interpreted these results as an indication that early social conditions represent a social stress resulting in a reduction of the overall reproductive resources up to the first egg laying.